Randomised controlled trial of interferon alfa 2A (rbe) (Roferon-A) for the treatment of chronic hepatitis B virus (HBV) infection: factors that influence response. Issue 8 (August 1989) - Brook, M G; McDonald, J A; Karayiannis, P; Caruso, L; Forster, G; Harris, J R; Thomas, H C
Abstract : In a randomised controlled trial recombinant interferon alpha 2A (Roferon-A, rIFN alfa A) given at a dosage of 10 million units (MU)/m2 thrice weekly for six months was significantly better (p less than 0.02) than no treatment in producing a sustained loss of hepatitis Be antigen (HBeAg) in hepatitis B virus (HBV) chronic carriers. Although lower doses (5 MU/m2 and 2.5 MU/m2) also produced some responses, the seroconversion rate was not significantly greater than that observed in the control group. Sixteen of the 45 patients receiving interferon were human immunodeficiency virus (HIV) antibody positive: none of these responded. Forty one per cent of the anti-HIV negative patients receiving interferon (12/29, p less than 0.005) lost HBeAg and 17% (5/29) lost hepatitis B surface antigen (HBsAg). The response rate among these anti-HIV negative patients receiving at least three months therapy was 46% and 19% respectively. Low pretreatment HBV-DNA and absence of anti-HIV were the only significant independent variables predicting response to therapy (p less than 0.03 and p less than 0.05 respectively). In six patients, neutralising antibodies to alpha interferon were detected during therapy, the majority being non-responders.